2012
DOI: 10.1007/s00380-012-0285-y
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory activation following interruption of long-term cardiac resynchronization therapy

Abstract: Previous observations suggest that cardiac resynchronization therapy (CRT) may exert an anti-inflammatory effect. The objective of this study was to evaluate the effect of temporary interruption of long-term CRT on plasma concentrations of proinflammatory cytokines and brain natriuretic peptide (BNP). The study group consisted of 54 patients (32 male and 22 female, mean age 64 years) with chronic heart failure (HF) treated with CRT. BNP, high-sensitivity C-reactive protein (hs-CRP), interleukin 6 (IL-6), and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…However, trials with unchanged levels of CRP have also been reported . In an interesting study by Rubaj et al ., it was demonstrated that serum CRP increased if the CRT was inactivated for just 48 h, and then decreased again following reactivation of the pacemaker . The same pattern was seen for IL‐6.…”
Section: Heart Failure Inflammation and Resynchronizationmentioning
confidence: 62%
See 1 more Smart Citation
“…However, trials with unchanged levels of CRP have also been reported . In an interesting study by Rubaj et al ., it was demonstrated that serum CRP increased if the CRT was inactivated for just 48 h, and then decreased again following reactivation of the pacemaker . The same pattern was seen for IL‐6.…”
Section: Heart Failure Inflammation and Resynchronizationmentioning
confidence: 62%
“…Several small and medium‐sized trials have shown a reduction in inflammatory mediators when heart failure patients are treated with CRT . In some of the studies, this is true only for patients defined as responders by predefined criteria .…”
Section: Heart Failure Inflammation and Resynchronizationmentioning
confidence: 99%
“…In clinical settings, cytokines including IL6 are acutely elevated during ST-or non-ST-elevation acute coronary syndromes (De Servi, et al, 2014;Neumann, et al, 1995). Markers of inflammation are also elevated in heart failure which can be reduced by cardiac resynchronization therapy (Rubaj, et al, 2013).…”
Section: Inflammatory State Prior To Surgerymentioning
confidence: 99%
“…Although in general natriuretic peptides and neopterin track with changes in myocardial function 22, 27 , dissociation in serum neopterin or inflammatory marker levels and B-type natriuretic peptide has been previously observed following improvements in hemodynamics following pacing therapy 28 . Our relatively stable ambulatory patient population with a relatively low range of natriuretic peptide levels may also dampen such association.…”
Section: Discussionmentioning
confidence: 99%